Citrus viroids in tunisia: prevalence and molecular characterization - Najar, Asma; Hamdi, I.; Varsani, A.; Durán-Vila, Núria (Springer, 2020)
A field survey was conducted in commercial orchards of Cap Bon region and at the INRAT citrus collection to identify the prevalence of citrus viroids in Tunisia. Samples were collected from 202 trees grafted on sour orange (Citrus aurantium L.) including 35 common mandarin and 40 Cassar clementine trees showing cachexia symptoms. Sequential PAGE (sPAGE) analysis and molecular hybridization using viroid-specific probes revealed that all plants were infected with at least two viroids. Citrus exocortis viroid (CEVd), hop stunt viroid (HSVd) and citrus dwarfing viroid (CDVd) were found to be widespread and accounted for 70.3%, 72.3% and 78.2% of the tested trees, respectively. Citrus bent leaf viroid (CBLVd) and citrus bark cracking viroid (CBCVd) were found in 28.2% and 3.0% of trees, respectively. The most frequent viroid combinations found were CEVd+HSVd+CDVd (34.7%) and HSVd+CDVd (22.3%). Other combinations such as CBLVd+HSVd+CDVd (12.9%), CEVd+CBLVd+HSVd (11.9%) and CEVd+CDVd (10.8%) were less frequent. CEVd and CDVd isolates were RT-PCR amplified, cloned and sequenced, then compared with sequences from other parts of the world deposited in GenBank. The three CEVd clones sequenced had 99% similarity with each other and shared ca. 99% similarity with those from Iran, Greece, and Syria. CDVd isolates were 100% similar and shared >96% similarity with other isolates from Brazil, Cyprus, Greece, Uruguay, Israel and Spain.